2020
DOI: 10.1016/j.ajpath.2019.09.011
|View full text |Cite|
|
Sign up to set email alerts
|

Ferroptosis Affects the Progression of Nonalcoholic Steatohepatitis via the Modulation of Lipid Peroxidation–Mediated Cell Death in Mice

Abstract: kr.Oxidative stress and its associated lipid peroxidation play a key role in nonalcoholic steatohepatitis (NASH). Ferroptosis is a recently recognized type of cell death characterized by an iron-dependent and lipid peroxidationemediated nonapoptotic cell death. We demonstrate the impact of ferroptosis on the progression of NASH induced by methionine/choline-deficient diet (MCD) feeding for 10 days. RSL-3 (a ferroptosis inducer) treatment showed decreased hepatic expression of glutathione peroxidase 4 (GPX4) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(170 citation statements)
references
References 41 publications
5
144
0
Order By: Relevance
“…Qi et al showed that ferroptosis leads to a diminished hepatic expression of GPx4: experiments performed on MCD-fed mice revealed a reduced GPx4 expression after RSL-3 (a ferroptosis inducer) administration. Moreover, a higher amount of apoptosis inducing factors were found in mice liver, indicating that ferroptosis plays a key role in NASH-associated cell death [90]. On the other hand, the administration of a ferroptosis inhibitor, Liproxstatin-1, reduces hepatic lipid peroxidation and cell death [90].…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Qi et al showed that ferroptosis leads to a diminished hepatic expression of GPx4: experiments performed on MCD-fed mice revealed a reduced GPx4 expression after RSL-3 (a ferroptosis inducer) administration. Moreover, a higher amount of apoptosis inducing factors were found in mice liver, indicating that ferroptosis plays a key role in NASH-associated cell death [90]. On the other hand, the administration of a ferroptosis inhibitor, Liproxstatin-1, reduces hepatic lipid peroxidation and cell death [90].…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Moreover, a higher amount of apoptosis inducing factors were found in mice liver, indicating that ferroptosis plays a key role in NASH-associated cell death [90]. On the other hand, the administration of a ferroptosis inhibitor, Liproxstatin-1, reduces hepatic lipid peroxidation and cell death [90].…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Knockout of Ripk3 ameliorates liver injury in these mice (135). Ferroptosis is a type of programmed cell death dependent on iron, producing lipid peroxidation-mediated cell death in NASH (136). Although it remains unclear whether pyroptosis, the highly inflammatory form of programmed cell death, occurs during NASH, the pyroptotic effector gasdermin D (GSDMD) and its pyroptosis-inducing fragment GSDMD-N are increased in human NASH.…”
Section: Liver Injurymentioning
confidence: 99%
“…The bona fide ferroptosis inhibitors ferrostatin-1 (Dixon et al, 2012) and liproxstatin-1 (Friedmann Angeli et al, 2014) exert their function as efficient radical trapping antioxidants (RTA), thereby preventing cellular autoxidation (Zilka et al, 2017). The protective effects of these compounds in mouse disease models include ischemia/reperfusion injuries of the kidney, liver, brain, heart, and intestine (Fang et al, 2019;Friedmann Angeli et al, 2014;Li et al, 2019aLi et al, , 2019bLinkermann et al, 2014;Tuo et al, 2017), acute renal failure (Friedmann Angeli et al, 2014), intracerebral hemorrhage (Li et al, 2017), neurodegeneration (Hambright et al, 2017), hemochromatosis (Wang et al, 2017), non-alcoholic steatohepatitis (Qi et al, 2020), and morphine tolerance (Chen et al, 2019), underlining the pathological role of lipid peroxidation and associated ferroptosis in numerous disease contexts. Vitamin E is perhaps the most efficient natural RTA found in organisms (Zilka et al, 2017).…”
Section: Disease Implications and Pharmacological Modulationmentioning
confidence: 99%